2022
DOI: 10.1186/s12894-022-01086-5
|View full text |Cite
|
Sign up to set email alerts
|

A new nomogram of urinary flow rate and volume based on multiple measurements per healthy adult Japanese men using a portable uroflowmeter (P-Flowdiary®)

Abstract: Background To develop a nomogram of urinary volume and flow based on the data of Japanese men without lower urinary tract symptoms and multiple flows per participant whose characteristics were clear. Methods Overall, 101 Japanese male volunteers without lower urinary tract symptoms aged between 20 and 59 years were enrolled. A portable uroflowmeter (P-Flowdiary®) was used to record urinary information (flow rate and volume) for 2 successive days. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Initially, a literature review was conducted to extract information on factors that facilitate and impede good urodynamic practice. The Pubmed, Web of Science, and Embase search engines were used with the following keywords: “urodynamic study,” “urodynamic study quality control,” “urodynamic study guidelines,” and “urodynamic artefacts.” Two different versions of UDS guidelines 15,16 and 15 studies on the UDS quality review in different regions 4,17–29 were included.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, a literature review was conducted to extract information on factors that facilitate and impede good urodynamic practice. The Pubmed, Web of Science, and Embase search engines were used with the following keywords: “urodynamic study,” “urodynamic study quality control,” “urodynamic study guidelines,” and “urodynamic artefacts.” Two different versions of UDS guidelines 15,16 and 15 studies on the UDS quality review in different regions 4,17–29 were included.…”
Section: Methodsmentioning
confidence: 99%
“…The Pubmed, Web of Science, and Embase search engines were used with the following keywords: "urodynamic study," "urodynamic study quality control," "urodynamic study guidelines," and "urodynamic artefacts." Two different versions of UDS guidelines 15,16 and 15 studies on the UDS quality review in different regions 4,[17][18][19][20][21][22][23][24][25][26][27][28][29] were included.…”
Section: Quick Checklist Design Processmentioning
confidence: 99%
“…Uroflowmetry is typically performed in an outpatient setting at designated facilities, where individuals urinate into a uroflow meter, mostly at a scheduled time. This 'unnatural' voiding on demand with varying bladder capacities may lead to significant test variability, suggesting the need for repeated uroflowmetry measurements and possible multiple clinic visits [9,14]. This has propelled the development of portable (home) uroflowmetry, facilitating a more natural urinary flow recording [9,15].…”
Section: Introductionmentioning
confidence: 99%
“…The HBU test provides a private and familiar environment that eliminates psychological and environmental influences on subjects. [2,3] Multivariate analysis revealed that age, VV, BMI, and eutocia were associated with the uroflow rate [Supplementary Table 3, http://links.lww.com/CM9/B973]. The correlation between age and uroflow rate remains controversial in current studies, but most studies have reached a consensus that uroflow decreases with age.…”
mentioning
confidence: 99%
“…The HBU test provides a private and familiar environment that eliminates psychological and environmental influences on subjects. [ 2 , 3 ]…”
mentioning
confidence: 99%